The role of management control systems in personnel controlling during COVID-19 pandemic - Niemiec, Andrzej; Golasińska, Małgorzata (Rola systemów kontroli zarządczej w controllingu personalnym podczas pandemii COVID-19, 2022)
The global crisis related to the COVID-19 pandemic engaged both academics and practitioners in studying new hypotheses and formulating new theories about the corporate financial situation. Unfortunately, according to the revised literature, the conclusions about big companies within a continuous production cycle during the pandemic are limited. The purpose of the article was to identify how COVID-19 influenced the human resources in these corporations, and what was the role of management control systems in the reduction of its negative impact. The pandemic’s parameters were correlated with human resources key performance indicators. The research method employed correlation and regression analysis with wild bootstrapping. The results showed that absences due to sickness were directly related to current holiday leaves, and were usually linked to the pandemic. This increases the impact of the COVID-19 pandemic on the availability of human resources. The increase of sickness absences resulted in the reorganization of work plans. The pandemic crisis emphasized the role of the management control system in personnel controlling. Fast and adequate information about sickness absence as well as introduced safety procedures resulted in no significant correlation between sickness absence and the COVID-19 statistics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2022; vol. 66, nr 1, s. 101-114
Keywords: performance management; COVID-19; human resources; zarządzanie dokonaniami; zasoby ludzkie